Balovsyak S.V., Derevyanchuk O.V., Kravchenko H.O., Kroitor O.P., Tomash V.V. Computer system for increasing the local contrast of railway transport images // Proceedings of SPIE. – 2021. – V. 12126. – P. 121261E1-7. - Balovsyak, Serhiy V.; Derevyanchuk, Oleksandr V.; Kravchenko, Hanna O.; Kroitor, Olga P.; Tomash, Vasyl V. (My University, 2021)
This article describes a computer system for increasing the local contrast of railway images obtained with digital video cameras. The local contrast of the images increases within the rectangular windows, for each of which the minimum and maximum brightness values are determined. Based on such extreme brightness values, the lower and upper envelope brightness of the image are calculated. By smoothing of the envelopes the artefacts that appear in the image after increasing the local contrast based on its envelopes are significantly reduced. The images are read to the control computer from USB video cameras. The software implementation of image processing is created in Python.
Keywords: digital image processing, local contrast, digital video camera